Effect of change in body weight and condition during the dry season on capacity for work of draft oxen - Bartholomew, P.W.; Khibe, T.; Little, D.A.; Ba, S. (Springer, 1993)
Work oxen supplemented at different levels during a feeding period of 3 months, were divided into 3 groups of average weight change -25, +35 and +70kg and worked under loadings of either 7.5 or 12.5 kgf/100kg of liveweight for 2 weeks, in order to assess the impact of dry season supplementation on capacity for work. At approximately equal levels of stress in work, manifest in maximum heart rate one minute after ceasing work, oxen with higher dry-season weight gain produced higher levels of work output, in proportion to their increased body weight. Rate of work and mean daily work output increased from the first to the second week of work, inspite of average daily weight losses of 2.63 kg throughout the period. Decline in rate of working through each day was continuous and essentially linear with relation to distance worked. The time taken to cover 1km increased at an average of 0.16 and 0.68 min/km for light and heavy loadings respectively.